Penelitian tentang Facebook - Kartini Kartini; Ineke Maili Ningrum; Juni Ervina Sari; Khoirunnisa Khoirunnisa (Universitas Muhammadiyah Enrekang, 2022)
Facebook is a social networking website where users can join communities such as cities, workplaces, colleges, and regions to connect and interact with other people. Compared to similar websites, Facebook provides complete facilities such as profile pages, photo and video albums, chats, notes, page applications, business applications, games, networks. using the type/approach of research in the form of library research. Literature study is a study that is used to collect information and data with the help of various materials in the library such as documents, books, magazines, historical stories, etc. So it can be concluded that if it is associated with the department of library science, the library uses social media as a medium for promotion, either promoting the collection or the services offered. However, with the development of a digital society that can hardly be separated from the internet, it seems that social media can be used more than just a promotional medium. Facebook as a medium to meet information needs because of the features that allow Facebook users to interact directly (real time), such as chatting, tagging photos, blogs, games, and status updates which are considered more up-to-date than other media.